Watch out for ST-elevation myocardial infarction: a case report of ST-elevation in single-lead electrocardiogram tracing of a smartwatch. Issue 6 (18th November 2020) - Stark, Konstantin; Czermak, Thomas; Massberg, Steffen; Orban, Martin
Abstract: Background: It was recently demonstrated that the detection of atrial fibrillation based on heart rate tracking by optical sensors is feasible and reliable using the Apple Watch and the corresponding application. There are already a number of smartwatches and other wearable devices alongside the Apple Watch that can additionally record a single-lead electrocardiogram (ECG) and it is reasonable to expect this technology to become a standard feature, as is already the case with automated heart rate tracking. This could potentially have enormous impact regarding the early diagnosis of several cardiac diseases. Case summary: A 61-year-old male patient without previously known coronary artery disease was admitted with subacute ST-elevation myocardial infarction (STEMI) caused by occlusion of left anterior descending artery. Due to mildness of symptoms, the patient did only seek medical attention due to morphological changes in the single-lead ECG tracing acquired on his Apple Watch 5. The ECG recording of his smartwatch clearly showed ST-elevation, QRS widening, R-wave loss, and T-wave inversion. Coronary angiography revealed occlusion of the left anterior descending and recanalization was performed. The patient recovered without any complications and was discharged from the hospital 4 days after admission. Discussion: While the potential of ECG recordings by smartwatches to detect atrial fibrillation is currently under scientific investigation, this case highlights the possible potential of these devices to detect STEMI.